一新型深吃水平台的概念设计 - 李彬彬; 欧进萍 (船舶与海洋工程学报（英文版）, 2010)
U6; The authors analyzed requirements for a new deepwater platform, from conceptual design to hydrodynamic analysis. The design incorporated Deep Draft Multi-Spar (DDMS) that allowed easy fabrication, reduced costs, and provided favorable motion performance. It also provided a dry tree system and other benefits. The conceptual design process included dimension estimation, general arrangements, weight estimation, weight distribution, stability analysis, etc. A high order boundary element method based on potential theory and the modified Morison equation was used to predict the hydrodynamic and viscous effects of this new concept platform. The response amplitude operators (RAOs) were acquired and compared with those of a typical Truss Spar. The response of the platform to the JONSWAP spectra of 3 different extreme ocean conditions was analyzed to evaluate the seakeeping ability of the new concept. The results revealed favorable motion performance due to all the degrees of freedom available.